Ground reaction forces during double limb stances while walking in individuals with unilateral transfemoral amputation - Kobayashi, Toshiki; Koh, Mark W. P.; Jor, Abu; Hisano, Genki; Murata, Hiroto; Ichimura, Daisuke; Hobara, Hiroaki (Frontiers in Bioengineering and Biotechnology, 2023)
The asymmetrical gait of individuals with unilateral transfemoral amputation (uTFA) has been well documented. However, there is not a wealth of investigation into asymmetries during the double limb stance (DLS) depending on whether the intact or prosthetic limb is leading. The first aim of this study was to compare ground reaction forces (GRFs) during the DLS of individuals with uTFA depending on whether their intact (initial DLS) or prosthetic (terminal DLS) limb was leading. The second aim of this study was to compare the asymmetry ratio of GRFs during the DLS between individuals with and without uTFA. Thirty individuals, fifteen with uTFA and fifteen who were able-bodied, were recruited for this study. Each individual walked on an instrumented treadmill for 30 seconds at eight different speeds, ranging from 2.0 km/h to 5.5 km/h with 0.5 km/h increments. GRF parameters, temporal parameters, and asymmetry ratios of all parameters were computed from the data collected. The appropriate statistical analyses of all data based on normality were conducted to investigate the aims of this study. Significant main effects of speed, DLS, and their interactions were found for most parameters (p < 0.01 or p < 0.05). Individuals with uTFA spent a longer duration in terminal DLS than initial DLS at all tested speeds. They also experienced significantly higher peak vertical GRF during initial DLS compared to terminal DLS with increasing walking speed. However, during terminal DLS, higher anteroposterior GRF at initial contact was found when compared to initial DLS. Significant differences between individuals with uTFA and able-bodied individuals were found in asymmetry ratios for peak vertical GRF, anteroposterior GRF, anteroposterior shear, and mediolateral shear at all tested speeds. Asymmetrical loading persists in individuals with uTFA during DLS. Increasing walking speed increased GRF loading asymmetries, which may make individuals with uTFA more susceptible to knee osteoarthritis or other musculoskeletal disorders. Further study is necessary to develop ideal gait strategies for the minimization of gait asymmetry in individuals with uTFA.